Improving Mathematical Critical Thinking Among Junior Secondary Students: A Problem-Based Learning Approach to Algebraic Content - Usmiyatun; Dwi Juniati; Siti Khabibah (Universitas Negeri Surabaya, 2026)
The purpose of this research is to examine how the Problem-Based Learning (PBL) model can be effectively applied to foster critical thinking abilities in junior secondary students, particularly within the domain of algebra. This study employed a qualitative approach with a teaching experiment design conducted in Grade VII A (29 students) at SMP PGRI II Wajak over four sessions. Data were collected through observation, pretest-posttest, student worksheets (LKPD), and questionnaires about learning motivation. According to Facione, the tool used to evaluate critical thinking skills includes six indicators: The study’s findings indicate notable progress in students’ critical thinking skills across six core dimensions: interpretation, analysis, evaluation, inference (conclusion), explanation, and self regulation evident both in their problem-solving performance and throughout the learning process. Both the N-Gain results, which were categorized as high (62.07%) and medium (37.93%), and the observation results, which demonstrated the domination of the good to very good category during the third meeting, demonstrate this growth. These results suggest that using the PBL paradigm can enhance students' quantitative critical thinking abilities and possibly boost their enthusiasm to learn. This study suggests using PBL as an alternative learning approach focused on fostering the growth of higher order thinking abilities.